Application of high performance precast steel fiber thin plate to strengthen reinforced concrete beam. - Abd. Aziz, Farah Nora Aznieta (2012)
High Performance Fiber Reinforced Composites (HPFRC) has been investigated as an externally bonded strengthened material on reinforced concrete beams. The HPFRC is made with five percent volume fraction of short hooked end steel fibers embedded in 70 N strength self-compacting mortar (SCM). To facilitate ease of manufacture and construction, HPFRC material has been prefabricated as 25 mm thin precast plate. The experimental program was carried out on nine reinforced concrete beams with 21 pieces of precast HPFRC thin plates to study the possibility of using precast HPFRC as strengthening material for reinforced concrete beams. The precast HPFRC thin plates are jacketed onto new, damaged and pre-cracked reinforced concrete beams and subjected to flexural test until failure. To ensure a good bond, the concrete beam surfaces were roughened while the top surface of the precast HPFRC thin plates were sand blasted. These surfaces were secured to the sides or bottom of the beam, with a controlled gap of three to five mm to permit correct placement of epoxy resin.The experimental results witnessed an improvement in strength to all conditions of the reinforced concrete beams, However jointing HPFRC, by butting plates together, was found to be ineffective, resulting in inconsistent and complex behaviour. The joints exposed the strengthened beam to shear failure and prevented shear stresses from being transmitted smoothly across the shear surfaces.